The evaluation of jumping ability of male and female basketball players according to their chronological age and major leagues - Kellis, S. E.; Tsitskaris, G. K.; Nikopoulou, M. D.; Mousikou, K. C. (The Journal of Strength and Conditioning Research, 1999)
The purpose of our research was to evaluate and compare the jumping ability among male and female basketball players according to their chronological age and major league. The sample consisted of 379 basketball players, 214 men and 165 women, ranging from 13 to 30 years old. For the evaluation, an electronic contact mat was used. A series of five vertical jumps were performed: squat jump (SJ), countermovement jump (CMJ), drop jump (DJ), and rebound jumps for 15 seconds (RJ15s) and 30 seconds (RJ30s). A oneway analysis of variance was used for the comparison of the height of the jumps among sexes and major leagues. The results, as was expected, revealed statistically significant differences in the height of the jumps between the two sexes at all ages (p < 0.05). The only exception was the SJ at the age of 13 (p = 0.12). Regarding the male, major statistical differences were revealed between ages with respect to the older ages. It is remarkable that the ages, two by two consecutively, did not present statistically important differences in any of the jumps. Generally, an increasing tendency was observed in the height of the jumps in relation to chronological age. As far as the male leagues are concerned, statistical differences were observed between league C and A2 or B, especially in RJ30s, and between A2 and B, especially in SJ and CMJ with respect to the first ones mentioned (C in RJ30s and A2 in SJ and CMJ). Regarding the females, less statistically significant differences were observed among ages. An unsimilar course appeared with a declining tendency of the height of the jumps, especially at the age of 16. On the contrary, as far as females` competitive leagues are oncerned, no statistically significant differences were revealed in any of the jumps.